Effects of Urochloa humidicola on Plant Diversity in Native Grasslands in a Neotropical Wetland - Bao, Francielli [UNESP]; Assis, Marco Antonio [UNESP]; Arruda, Rafael; Pott, Arnildo (Springer, 2015)
Studies on species invasion in wetlands are fundamental to understanding the consequences of the introduction of exotic plants, which are often utilized in grasslands. The loss of native plant diversity is of increasing concern. We evaluated the effect of Urochloa humidicola on floristic similarity between native and cultivated grasslands and the differences in spatial distributions between species. To analyze the effect of seasonality, we collected samples at the end of flood and dry periods. In native grasslands and another area cultivated with U. humidicola, samples were collected at three elevations (bottom; intermediate; and top). We identified 90 species and observed a high similarity between the cultivated and native grassland during the flood period; both grasslands exhibited significant differences during the drought period. This difference was due to an increased presence of grasses, mainly U. humidicola, in the cultivated grassland. Increased similarity between bottom and intermediate elevations was due to an increased proportion of aquatic macrophytes. In contrast, the top elevation differed due to the contribution of terrestrial species. We conclude that the native and cultivated grasslands exhibit differences in vegetation composition and are primarily structured by seasonal flooding, and small variations in elevation promote zonation within the plant community.
Keywords: Exotic species; Flood; Floristic similarity; Plant invasion; Vegetation dynamics